Formation of pre-metastatic niches induced by tumor extracellular vesicles in lung metastasis. (February 2023) - Liu, Yuping; Mao, Dengxuan; Wang, Hong; Che, Xiaoyu; Chen, Yan
Abstract: There are a number of malignant tumors that metastasize into the lung as one of their most common sites of dissemination. The successful infiltration of tumor cells into distant organs is the result of the cooperation between tumor cells and distant host cells. When tumor cells have not yet reached distant organs, in situ tumor cells secrete extracellular vesicles (EVs) carrying important biological information. In recent years, scholars have found that tumor cells-derived EVs act as the bridge between orthotopic tumors and secondary metastases by promoting the formation of a pre-metastatic niche (PMN), which plays a key role in awakening dormant circulating tumor cells and promoting tumor cell colonization. This review provides an overview of multiple routes and mechanisms underlying PMN formation induced by EVs and summaries study ﬁndings that underline a potential role of EVs in the intervention of lung PMN, both as a target or a carrier for drug design. In this review, the underlying mechanisms of EVs in lung PMN formation are highlighted as well as potential applications to lung metastasis diagnosis and treatment. Graphical Abstract: ga1